Assessment of National CLAS Standards in Rural and Urban Local Health Departments in Kentucky. Issue 6 (November 2016) - Gómez, María L.; Charnigo, Richard; Harris, Torrie T.; Williams, John C.; Pfeifle, William
Abstract : Context: Findings from the Centers for Disease Control and Prevention suggest that addressing persistent health disparities based on race and ethnicity must become a national priority. The field of cultural and linguistic competency has gained national attention by improving access to and quality of health care, patient-provider communication, health outcomes, and health equity for minority groups and other vulnerable or special needs populations. Objectives: (1) To measure how local health departments (LHDs) in Kentucky comply with the National Standards for Culturally and Linguistically Appropriate Services (CLAS); and (2) to provide policy recommendation based on the findings. This study is the first to assess a statewide public health system under the lens of CLAS. Design: Analysis of cross-sectional survey. Setting: Electronic surveys administered to LHD administrators in Kentucky. Participants: Public health directors, nurse leaders, and program managers. Main Outcome Measure: Levels of compliance with various CLAS standards were examined for rural and urban counties using a novel scoring method. Results: A total of 159 LHD administrators received the survey. Response rate was 67% (106 participants). Rural and urban LHDs achieved moderate compliance on domains of plans and policies, quality monitoring and improvement for needs assessment, management information systems for clients, and staff training and development. Both geographic groups exhibited lesser compliance on domains of organizational governance, culturally inclusive health care environment for educational materials, and diversity of personnel recruitment. Conclusion: County and district LHDs in Kentucky have implemented activities and policies that comply with CLAS standards at levels that vary by domain. Areas requiring particular attention include organizational governance, culturally inclusive health care environment for educational materials, and diversity of personnel. Improvements in these areas may help LHDs better meet the needs of vulnerable populations, racial and ethnic minorities, and special needs groups. CLAS practices may allow organizations to adhere to national public health accreditation standards. Abstract : Supplemental Digital Content is Available in the Text.This article describes how local health departments in Kentucky comply with national CLAS standards and provides policy recommendation based on the findings.